Makna Pemilu: Ketidakrunutan Arti Penting Pemilu Bagi Pemilih - Ulfah, Irma Fitriana; Setiawan, Andi; Afala, La Ode Machdani; Garner, Andrew Douglas; Seitz, Thomas R; Tawakkal, George (CosmoGov: Jurnal Ilmu Pemerintahan, 2021)
gb777